1980
DOI: 10.1002/hlca.19800630407
|View full text |Cite
|
Sign up to set email alerts
|

Alcaloïdes bis‐indoliques de Catharanthus ovalis

Abstract: I P H 3 BI (56,O)Bi-1 (17,5) Methanol pH 4,5 Bz (55.5) B2-1 (12,7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Surprisingly, besides starting material and palmatine (3a), we obtained the ketolactam saulatine (23a), which had been first reported in 1984 as a result of work on Abuta bullata (Menispermaceae) (27). One year before that time, two independent studies had found the related ketolactam puntarenine (23) in the course of investigations of the contents of B. actinacantha (28,29). Since we had started our chromatographic study of palmatine-chloroform with clean material and since we had never previously isolated saulatine in our laboratory, it can only be concluded that saulatine (23a) and, by extension, puntarenine (23) are artifacts.…”
Section: Mementioning
confidence: 78%
See 1 more Smart Citation
“…Surprisingly, besides starting material and palmatine (3a), we obtained the ketolactam saulatine (23a), which had been first reported in 1984 as a result of work on Abuta bullata (Menispermaceae) (27). One year before that time, two independent studies had found the related ketolactam puntarenine (23) in the course of investigations of the contents of B. actinacantha (28,29). Since we had started our chromatographic study of palmatine-chloroform with clean material and since we had never previously isolated saulatine in our laboratory, it can only be concluded that saulatine (23a) and, by extension, puntarenine (23) are artifacts.…”
Section: Mementioning
confidence: 78%
“…Similarly, the ketolactam magallanesine (25), obtained as part of a study of B. darwinii (30), can be formed as shown in Scheme 2 through the intermediacy of the dichloro adduct 24 derived from oxyberberine (5) (31). Saulatine (23a), puntarenine (23), and magallanesine (25) are thus interesting instances of artifacts formed from CHC13, even though they contain no chlorine.…”
Section: Mementioning
confidence: 99%
“…A 'H-nmr spectrum at 270 MHz indicated the dimeric nature of the molecule. Thus, many of the proton resonances of the alkaloid vindoline (38,39) were observed in a repeated or more complex manner (e.g., 18-CH3, 17-OCOH3, N-CH3, ArOCH3, 15-H, 9-H, and 12-H) and indicated adose resemblance to the alkaloid vindolicine (4). Previous work (16,17,40) on this alkaloid had suggested that it was a dimer of vindoline joined through C-10 by a methylene group.…”
Section: Structure Confirmationmentioning
confidence: 99%